Review: A working checklist of the freshwater fish diversity for habitat management and conservation work in Sabah, Malaysia, North Borneo - CASEY KEAT-CHUAN NG; FATIMAH ABDULLAH; HELENA BIUN; MOHAMMAD KHADAFI IBRAHIM; SHUHADAH MUSTAPHA; AHEMAD SADE (Biodiversitas Journal of Biological Diversity, 2017)
Ng CKC, Abdullah F, Biun H, Ibrahim MK, Mustapha S, Sade A. 2017. Review: A working checklist of the freshwater fish diversity for habitat management and conservation work in Sabah, Malaysia, North Borneo. Biodiversitas 18: 560-574. Prioritization of freshwater habitat management and conservation is dependent on the availability of species baseline information at regional level. However, such information has not been updated since 2002 in Sabah. Thus the objective of this paper is to present the latest working checklist of freshwater ichthyofauna known so far in the state. A literature review of 68 studies was conducted focusing on the latest valid binomial nomenclature, locality and conservation status. A total of 166 valid species, namely 150 native species and 16 introduced species, were deduced from the literature. Native species comprised of 10 orders, 27 families and 75 genera while introduced species were from four orders, seven families and 14 genera. The review revealed 103 species (68.6% of native species) were yet to be assessed for the IUCN Red List and 11 species (7.3%) were identified as Data Deficient by IUCN. Some taxonomic discrepancies were also found and discussed. Many areas in Sabah remain poorly inventoried due to unequal sampling effort, biophysical and cultural challenges. The species list proposed herein is tentative at best and the number of species is expected to increase as more surveys are conducted in the near future.